Exposure to Major Vector-Borne Diseases in Dogs Subjected to Different Preventative Regimens in Endemic Areas of Italy - Mariasole Colombo; Simone Morelli; Giulia Simonato; Angela Di Cesare; Fabrizia Veronesi; Antonio Frangipane di Regalbono; Laura Grassi; Ilaria Russi; Pietro Giorgio Tiscar; Giulia Morganti; Jasmine Hattab; Valeria Rizzo; et al. (Pathogens, 2021)
Vector-borne diseases (VBDs) are globally widespread arthropod-transmitted diseases with a significant impact on animal and human health. Many drivers have recently spurred the geographic spread of VBDs in dogs. This study has evaluated the exposure to most important VBDs in dogs under different preventative treatments in different regions of Italy, i.e., Veneto, Friuli Venezia-Giulia, Umbria, Giglio Island (Tuscany), Abruzzo and Latium. Serological analyses were performed to detect antibodies against Leishmania infantum, Babesia canis, Anaplasma phagocytophilum/Anaplasma platys, Ehrlichia canis/Ehrlichia ewingii, Borrelia burgdorferi, Rickettsia conorii and the circulating antigen of Dirofilaria immitis. Dogs were categorized according to the treatment schedule usually received, and the association between seropositivity and possible risk factors was statistically evaluated. Overall, 124/242 (51.2%) dogs tested positive for at least one pathogen, while 34 (14.0%) were exposed to two or more pathogens. The most detected seropositivity was against R. conorii, followed by Anaplasma spp., L. infantum, B. canis, and the other pathogens under study. Significant statistical associations were found according to geographical provenance, history of tick infestation, lifestyle and inadequate prophylactic treatments. Random/irregular treatments have been identified as a clear risk factor. These results show that adequate prophylactic treatment protocols are overlooked by dog owners, despite the availability of several effective products, with possible implications in veterinary medicine and on public health.